EFEKTIVITAS MODEL TTW BERBANTUAN SOFTWARE FOCUSKY TERHADAP HASIL BELAJAR EKONOMI SISWA SMA MUJAHIDIN PONTIANAK - Novitasari, Devi; Witarsa, Witarsa; Achmadi, Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aimed in order to know the effectiveness of the implementation of think, talk, write learning model with focusky software on student learning outcomes  XI IPS economic subjects at SMA Mujahidin Pontianak. The research method is quasy experimental design with nonequivalent control grup design. The Subject of this research is XI  IPS 1 as experiment class and XI IPS 2 as controlled class which the total is 68 students. The technique of data collection were done by direct observation techniques, measuring techniques, and documentary study techniques. Data collection tool which is observation sheet, multiple choice test and documentation and analayzed by descriptive analysis, descriptive statistical analysis and  effect size. According to the research findings, the learning process in the experiment class was active and students oriented. The result of data analysis showed the average score of students' learning outcomes of experiment class for  pre-test is 39.84 and for  post-test is 75.47 with 66% completeness of 32 students. The t test (independent sample t test) obtained a sig (2-tailed) value of 0.009 less than 0.05 which means Ho is rejected and Ha accepted, in other words the learning model of think, talk, write with focusky software effective on learning outcomesThe value of effect size is 0.67, included in the medium category.Keyword: Effectiveness, Think Talk Write, Focusky, Learning Outcomes